ANALISIS PENGARUH PENDAPATAN, PENDIDIKAN, PEKERJAAN DAERAH ASAL, JUMLAH TANGGUNGAN DAN STATUS PERKAWINAN TERHADAP KEPUTUSAN MIGRASI SIRKULER KE KOTA SEMARANG (STUDI KASUS: KECAMATAN TEMBALANG DAN PEDURUNGAN) - Hasudungan Pangaribuan, Kaisar; Retno Handayani, Herniwati (Diponegoro Journal of Economics, 2013)
This study aimed to analyze the effect of wage, education, job village, number of dependents and marital status against migration decision to Semarang City. Disparity income between village and city is one of a reason from migrant to move to city with a hope will get bigger wage. The limitation of job in village also affect peopleâ€™s decision to migrate to the city.This research analyzed using â€œlogistic regression technicâ€ thus Binary Logistic Regression. This technic used because the dependent variable is variable with two categories or binomial, means 1 is for willingness to stay and 2 is the opposite.The result of analysis Binary Logistic Regression is explain that influenced factors to circuler migration are wage variable (WAGE) with significant value (p-value 0,006) has a positive impact, education variable (EDU) with significant value (p-value 0,036) has a positive impact, and job in village variable (JOBVLG) with significant value (p-value 0,005) has a negative impact. Generally Binary Logistic Regression Model that used to explain factors of migration decision has a accuracy 70%. This is showing that respondent will be mostly having a circuler migration to earn money for family expenses.Â